Effects of counter-rotation position on knee/hip angulation, center of mass inclination, and edging angle in simulated alpine skiing - Yoon, S.; Kim, J.-H.; Park, J.-H.; Ryu, J.; Park, S.-K.; Kim, J.-N. (Korean Journal of Sport Biomechanics, 2017)
Objective: To investigate rotation movement of segment for performing each position and its effect on knee/hip angulation, COM inclination, and edging angle changes. Method: Twelve Alpine skiers (age: 25.8±4.8 years, height: 173.8±5.9 cm, weight: 71.4±7.4 kg, length of career: 9.9±4.6 years) participated in this study. Each skier was asked to perform counter-rotation, neutral, and rotation positions. Results: Shank and thigh were less rotated in the counter-rotation position than in other positions, whereas the trunk and pelvis were more counter-rotated (p<.05). Hip angulation, COM inclination, and edging angle were significantly greater in the counter-rotation position than in other positions (p<.05). Conclusion: Our finding proved that the counter-rotation position increases hip angulation, COM inclination, and edging angle. Consequently, we suggest that skiers should perform counter-rotation of the trunk and pelvis relative to the ski direction in the vertical axis for the counter-rotation position. Further analysis will continue to investigate the effects of the counter-rotation position in real ski slope with kinetic analysis.